Impacts of sodium chlorite combined with calcium chloride, and calcium ascorbate on microbial population, browning, and quality of fresh-cut rose apple - Mola, Sunthon; Uthairatanakij, Apiradee; Srilaong, Varit; Aiamla-or, Sukunya; Jitareerat, Pongphen (Agriculture and Natural Resources, 2016)
Microbial activity and browning were minimized and fresh-cut rose apple quality was maintained using sodium chlorite (SC) combined with calcium chloride (CC) and calcium ascorbate (CaAs) and by investigating the optimal concentration and dipping time of SC for inhibiting microbial activity and browning. Fresh-cut rose apple samples were dipped in SC solution at 100 mg/L and 200 mg/L for 1 min and 3 min, with filtered water and non-dipped samples as controls. All samples were kept at 4 ± 2 oC for 9 d. The results showed that 200 mg/L SC for 3 min was the best treatment to inhibit microbial growth (total bacteria, yeast and molds, Escherichia coli and coliforms), delay browning and polyphenol oxidase (PPO) activity of fresh-cut rose apples, but could not maintain the fresh firmness. A firmness experiment was conducted by dipping fresh-cut rose apples in 200 mg/L SC and in 200 mg/L SC combined with 20 g/L CC and 20 g/L CaAs (SC + CC + CaAs) for 3 min before storage at 4 ± 2 oC for 9 d. Samples immersed in filtered water were used as the control. The combined treatment delayed microbial contamination and browning by reducing the PPO activity and the accumulation of phenolic content, and maintained the fresh firmness of fresh-cut rose apples. Thus, the combination treatment of SC + CC + CaAs solution can protect fresh-cut rose apples against microbial contamination and delay browning and maintain firmness.